IJCM_251A: An Assessment of client satisfaction and factors associated with services provided by Urban Primary Health Centres (UPHCs) of Raipur city. - Lakra Melisha Shilpy; Jain Kamlesh; Verma Smita; Dengani Monika (Wolters Kluwer Medknow Publications, 2024)
Background: Healthcare is an important aspect of concern for individuals, involving a range of services provided to individuals, families, or communities by healthcare professionals. The objective is to promote, maintain, monitor, or restore health. Client satisfaction in health care is an important indicator used to measure the quality of services provided by the health care facilities. It is a key outcome of health care and use of services. The assessment of patient satisfaction extends across various dimensions of health services, encompassing factors such as the availability, accessibility, and convenience of services consisting of physician, pharmacy, nurses and registration services. Objective: To assess the client satisfaction about the services provided by Urban Primary Health Centres. Methodology: This is a cross-sectional observational study conducted in the Urban Primary Health Centres of Raipur city, Chhattisgarh. The Urban Primary Health Centres (8 UPHCs) are selected by simple random sampling by lottery method and the study subjects (425 study subjects) are selected by consecutive sampling. Predesigned, pretested questionnaire of socio demographic profile and predesigned, pretested, semi-structured questionnaire on client satisfaction are used for data collection which consisted of questions regarding Physical facilities, Physicians services, Nurses services, Pharmacy services, Registration services, Accessibility to services and Convenience. After collection of data, compilation of data will be done using Microsoft excel sheet. Data will be analysed using suitable statistical software (SPSS version 21) Results: The majority of study participants, 324 (76.2%) were females. The study showed that most, 274 (64.5%) of the study participants were between the age of 21 to 40 years. The study subjects showed satisfaction of 59.8%, 51.5%, 44.2%, 43.8%, and 42.6% for nurse's services, accessibility to services, physician services, pharmacy services, and registration services respectively and 45.2% satisfaction for both convenience and physical facilities. Conclusion: The findings from this study showed that overall satisfaction with the services provided was above average. However, there was dissatisfaction observed with some services. The evaluation of patient satisfaction with healthcare services has emerged as a crucial concern. Effectively addressing this matter could serve as an important tool for healthcare providers, providing insights into both their areas for improvement and successes.